Peran Guru dalam Upaya Meningkatkan Kualitas Baca Tulis Al Qur’an di TPQ Al-Chusnaniyah Surabaya - Qurrotul Ainy; Iksan Kamil Sahri (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
Abtsract The main factor in improving the quality of learning of reading and writing Qur'an among Muslims is human resources. In the context of education, teachers are the main actor to be improved. The aims are better output of learning. Teachers in the context of Islam is a guide for students. This study aims to determine how the teacher's role in an effort to improve the quality of reading the Qur'an at TPQ Al-Chusnaniyah Surabaya. To answer this, the researchers conducted a descriptive qualitative research with the methods of interview, observation, and documentation as the data collection technique. The finding is that in teaching and learning activities to read and write the Qur'an, the learning process becomes very important, especially in terms of giving concrete examples to students. The results of the teacher's role in efforts to improve learning activities to read and write the Qur'an are considered satisfactory, as evidenced by the increase in the number of students who can read the Qur'an properly and correctly.